2021
DOI: 10.1088/1748-9326/ac1fbb
|View full text |Cite
|
Sign up to set email alerts
|

Future climate change significantly alters interannual wheat yield variability over half of harvested areas

Abstract: Climate change affects the spatial and temporal distribution of crop yields, which can critically impair food security across scales. A number of previous studies have assessed the impact of climate change on mean crop yield and future food availability, but much less is known about potential future changes in interannual yield variability. Here, we evaluate future changes in relative interannual global wheat yield variability (the coefficient of variation (CV)) at 0.25° spatial resolution for two representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 84 publications
1
32
1
3
Order By: Relevance
“…El clima es uno de los factores más importantes para el desarrollo de los cultivos, y afecta su producción y rendimiento (Galindo, 2009;Carrasco, 2016;Benique, 2019;Villegas, 2021) pudiendo afectar gravemente la seguridad alimentaria en todas las escalas, pues afecta la distribución espacial y temporal de los rendimientos de los cultivos (Martins et al,2018;Liu et al, 2021); por lo que, para mantener su rendimiento, deben encontrarse dentro de los márgenes apropiados de temperatura y precipitaciones en sus diferentes Por otro lado, su proyección de rendimiento al 2029, tal como se ilustra en la figura 3, muestra una tendencia negativa, reduciéndose a 1.12t/ha. En el camu-camu, la variable determinante sobre su rendimiento, es la precipitación pluvial (tabla 2); lo cual refleja la necesidad hídrica propia de su fisiología y hábitat (Imán, 2001); aun cuando los requerimientos de precipitación pluvial son altos (2,500 a 4,000 mm/año) en suelos aluviales, su estrecha cercanía a fuentes de agua puede asegurar la mayor parte de sus requerimientos suministrados por el sustrato donde se desarrolla; sin embargo, en los suelos de altura, en los meses de menor precipitación o de veranos prolongados, la planta llega a presentar marchitez (Pinedo el al., 2001), situación a la que algunos clones como en el E3-F7, presenta cierta tolerancia a medida que crece y se desarrolla, pudiendo ser una alternativa a esta situación negativa (Aguirre el al.…”
Section: Resultados Y Discusiónunclassified
“…El clima es uno de los factores más importantes para el desarrollo de los cultivos, y afecta su producción y rendimiento (Galindo, 2009;Carrasco, 2016;Benique, 2019;Villegas, 2021) pudiendo afectar gravemente la seguridad alimentaria en todas las escalas, pues afecta la distribución espacial y temporal de los rendimientos de los cultivos (Martins et al,2018;Liu et al, 2021); por lo que, para mantener su rendimiento, deben encontrarse dentro de los márgenes apropiados de temperatura y precipitaciones en sus diferentes Por otro lado, su proyección de rendimiento al 2029, tal como se ilustra en la figura 3, muestra una tendencia negativa, reduciéndose a 1.12t/ha. En el camu-camu, la variable determinante sobre su rendimiento, es la precipitación pluvial (tabla 2); lo cual refleja la necesidad hídrica propia de su fisiología y hábitat (Imán, 2001); aun cuando los requerimientos de precipitación pluvial son altos (2,500 a 4,000 mm/año) en suelos aluviales, su estrecha cercanía a fuentes de agua puede asegurar la mayor parte de sus requerimientos suministrados por el sustrato donde se desarrolla; sin embargo, en los suelos de altura, en los meses de menor precipitación o de veranos prolongados, la planta llega a presentar marchitez (Pinedo el al., 2001), situación a la que algunos clones como en el E3-F7, presenta cierta tolerancia a medida que crece y se desarrolla, pudiendo ser una alternativa a esta situación negativa (Aguirre el al.…”
Section: Resultados Y Discusiónunclassified
“…Globally, climate change affects the spatial and temporal distribution of crop yields, which can critically impair food security [29]. However, the identification of high-yielding drought-tolerant genotypes remains a proficient approach to cope with climate challenges [30].…”
Section: Discussionmentioning
confidence: 99%
“…According to this, some regions will have both increases in rainfall and temperature, which is important to grow drought and high-temperature tolerant varieties. Liu et al [29] indicated that over 60% of harvested areas could experience significant changes in interannual yield variability under a high-emission scenario by the end of the 21st century (2066-2095). The results from several studies, such as [29,31,32], have indicated substantial changes in interannual yield variability as a result of climate change, and that the sign and magnitude of change varied by production region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous global-scale crop yield datasets including Harvester Area and Yields of 175 crops (M3Crops) (Monfreda et al, 2008), Spatial Production Allocation Model (SPAM) (You and Wood, 2006;Yu et al, 2020), Global Dataset of Historical Yields of Major Crops (GDHY) (Iizumi et al, 2014;Iizumi and Sakai, 2020), and Global Gridded Crop Model Intercomparison (GGCMI) phase 1 (Müller et al, 2019), have 60 been produced and widely used in many studies (Folberth et al, 2020;Kaltenegger and Winiwarter, 2020;Iizumi et al, 2021;Lin et al, 2021;Liu et al, 2021b). However, due to the different research goals and technical restrictions, their spatial resolutions are relatively coarser (~10km for M3Crops and SPAM; ~55km for GDHY and GGCMI phase 1) and temporal resolutions are mostly annual (Laborte et al, 2017).…”
Section: Introduction 45mentioning
confidence: 99%